PENGARUH JENIS ATAP RUMAH TERHADAP PENURUNAN INTENSITAS MEDAN MAGNET DI BAWAH SUTT 150 KV - Erlyn Yulia; sudarti sudarti; yushardi yushardi (JURNAL PEMBELAJARAN FISIKA, 2017)
The current study is based on the needs of human life that cannot be separated from the role of electricity. This is why the demand for electricity is getting increased, so it requires the construction of transmission channels, one of them is SUTT. Without realizing it, the channel emits magnetic field. The exposure to magnetic field generated by SUTT has extremely low frequency since the rate commonly used in Indonesia is 50 Hz. The purpose of the current study was to find out the distribution pattern of magnetic field radiation intensity below SUTT 150 kV and the influence of roof types to the decrease of ELF magnetic field intensity by SUTT 150 kV. The study design was field experiment using measuring devices of magnetic field with EMF-827. The results confirmed that the area under the phase wires had the greatest magnetic field intensity, that was almost 70 times bigger than that of the natural magnetic field intensity. Based on the data collection, the use of roof barrier did not effect to the decrease of the magnetic field intensity because the decrease had segnificantly occured at farther distance from the phase wires without using roof barriers. All the results of magnetic field intensity measurements was still below the limit allowed by WHO. The results of the current study can be used as new understanding for Indonesians, especially those who still live under the transmission line